1984
DOI: 10.1136/bmj.288.6424.1119
|View full text |Cite
|
Sign up to set email alerts
|

Negative selection of patients for dialysis and transplantation in the United Kingdom.

Abstract: 33 Topping DL, Weller RA, Nader CJ, et al. Adaptive effects of dietary ethanol in the pig: changes in plasma high-density lipoproteins and fecal steroid excretion and mutagenicity. Am 7 Clin Nutr 1982;36: 245-50. " Yoshida T, McCormick WC, Swell L, Vlahcevic ZR. Bile acid metabolism in cirrhosis. IV. Characterization of the abnormality in deoxycholic acid metabolism. Gastroenterology 1975 ;68 :335-41. si Williams CN, Scallion SM, McCarthy SC. A diet containing highly refined carbohydrate will adversely change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(30 citation statements)
references
References 5 publications
1
28
1
Order By: Relevance
“…In this patient group, dialysis is likely to be for life, with only 15% of all adult transplantations taking place in those aged ≥65 years in the US in 2008 [1]. Twenty-five years ago, 45.1% of UK nephrologists responding to a survey would not offer renal replacement therapy to a 50-year-old man with ischaemic heart disease [2]. In contrast, 15 years later, dialysis was available in the UK for high-risk patients (higher age, severe comorbidities and dependent in relation to functional status) despite a low 1-year survival of 19.2% [3].…”
Section: Dialysis In Older People: a Growing Populationmentioning
confidence: 99%
“…In this patient group, dialysis is likely to be for life, with only 15% of all adult transplantations taking place in those aged ≥65 years in the US in 2008 [1]. Twenty-five years ago, 45.1% of UK nephrologists responding to a survey would not offer renal replacement therapy to a 50-year-old man with ischaemic heart disease [2]. In contrast, 15 years later, dialysis was available in the UK for high-risk patients (higher age, severe comorbidities and dependent in relation to functional status) despite a low 1-year survival of 19.2% [3].…”
Section: Dialysis In Older People: a Growing Populationmentioning
confidence: 99%
“…Dialysis for the older and frailer individual is a comparatively new treatment option. As late as 1984, Challah et al [4] reported from a survey that 45% of a sample of UK nephrologists would decline dialysis in a 50-year-old man with ischaemic heart disease. Less than 20 years later outcomes of octogenarians on dialysis were being published [5].…”
Section: Introductionmentioning
confidence: 99%
“…The doubling of dialysis provision during the 1980s in the UK was almost entirely through CAPD, with little or no choice offered to patients, whereas transplantation rates increased significantly. The concept of negative selection was apparent, publicized in the national media, and described (25). Conclusions were made that under-referral from nonspecialists was a leading factor.…”
Section: History Of Dialysis In the Ukmentioning
confidence: 97%